Evaluating the Impact of Role Play on Literary Text Comprehension: An Experimental Study Using The Oracle of Cidino - Leader Hilongwa; Sivakumar Sivasubramaniam (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
The fundamental goal of roleplay is for students to become actively involved in the learning process, which results in better and deeper understanding. This study investigated the effectiveness of role-play in enhancing undergraduate students’ comprehension of The Oracle of Cidino by Nyathi (2003) through role-play as an instructional strategy. Grounded on the premise of the constructivist paradigm, this experimental design compared comprehension achievements between the control group that received traditional instruction and the experimental group that participated in role play to assess the extent to which role play influences students’ comprehension and academic performance. A convenient sampling technique was employed to select the study population. A sample of 83 student participants was selected using Yamane formular (1967). A computer-generated number was used to randomly assign 83 student participants into the control (n=42) and the experimental (n=41) groups. Data was collected through pre- and post-tests, and descriptive statistics were used to analyse data. The findings revealed that incorporating constructivist, participatory pedagogies such as role-play can enhance students’ academic performance by developing and supporting active learning environments like literature classrooms. The study recommends future research to examine pre-posttests through student discussion to justify their literary test answers and to teach literature through television to aid comprehension, engagement, and appreciation.